1993
DOI: 10.1111/j.1471-4159.1993.tb03641.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of [U‐13C]Glutamate in Astrocytes Studied by 13C NMR Spectroscopy: Incorporation of More Label into Lactate than into Glutamine Demonstrates the Importance of the Tricarboxylic Acid Cycle

Abstract: Primary cultures of cerebral cortical astrocytes were incubated with [U-13C]glutamate (0.5 mM) in modified Dulbecco's medium for 2 h. Perchloric acid (PCA) extracts of the cells as well as redissolved lyophilized media were subjected to NMR spectroscopy to identify 13C-labeled metabolites. NMR spectra of the PCA extracts exhibited distinct multiplets for glutamate, aspartate, glutamine, and malate. The culture medium showed peaks for a multitude of compounds released from the astrocytes, among which lactate, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
153
2
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(170 citation statements)
references
References 12 publications
13
153
2
2
Order By: Relevance
“…The presence of isotopomers from subsequent turns also showed that the carbon skeleton stayed in the TCA cycle. This confirms that the glutamate-glutamine cycle does not operate in a stochiometric fashion (McKenna et al, 1993(McKenna et al, , 1994Sonnewald et al, 1993a) and that glutamine is readily oxidized by cerebellar cultures for energy.…”
Section: C]glutamine Metabolismsupporting
confidence: 65%
“…The presence of isotopomers from subsequent turns also showed that the carbon skeleton stayed in the TCA cycle. This confirms that the glutamate-glutamine cycle does not operate in a stochiometric fashion (McKenna et al, 1993(McKenna et al, , 1994Sonnewald et al, 1993a) and that glutamine is readily oxidized by cerebellar cultures for energy.…”
Section: C]glutamine Metabolismsupporting
confidence: 65%
“…These data suggest either two segregated pyruvate pools or extremely slow pyruvate transamination relative to its conversion to lactate. Synthesis of pyruvate from lower specific activity (Table 4) TCA cycle derivatives (Cerdan et al, 1990;Hassel and Sonnewald, 1995;Sonnewald et al, 1993Sonnewald et al, , 1996 might supply an alanine precursor pool, but metabolism of neurotransmitter-derived glutamate is a less-likely source because labeled glutamate is not incorporated into alanine in cultured astrocytes (McKenna et al, 1996). Thus, use of lactate-or alanine-specific activity (which differs by almost twofold; Tables 3 and 4) to estimate the specific activity of pyruvate for calculation of TCA cycle fluxes might not be appropriate, depending on which pool reflects the true pyruvate precursor pool(s) for the TCA cycle(s) of interest.…”
Section: Lactate Accumulation Pyruvate Compartmentation and Metabolmentioning
confidence: 99%
“…However, more substantive explanations may also pertain, including the expression of other variant forms of GLT1 not yet recognized, or other transporters, such as EAAC1 (He et al, 2000), post-translational modification, or interacting proteins interfering with antibody binding. In addition, some axon terminals may use alternate pathways to resupply excitatory terminals with glutamate (Fonnum, 1984;Shank et al, 1989;Lehmann et al, 1993;Sonnewald et al, 1993;Westergaard et al, 1995;Hertz et al, 1999;Hassel and Brathe, 2000a,b).…”
Section: Glt1 Is Expressed In a Subpopulation Of Axon Terminalsmentioning
confidence: 99%